2021
DOI: 10.1039/d1cc06034a
|View full text |Cite
|
Sign up to set email alerts
|

Tetra- and hexanuclear string complexes of the coinage metals

Abstract: Tetranuclear homo- and heterometallic coinage metal complexes, as well as a hexanuclear gold complex, were synthesized. All feature a metal string structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 57 publications
3
22
0
Order By: Relevance
“…Despite the fact, that transition metal complexes of PNP-type ligands such as Ph 2 PNRPPh 2 (R = Et, 15 C 6 H 5 , 16 2,6-Me 2 C 6 H 3 , 16,17 C 6 H 3 N 2 S), 18 and coordination complexes of related PNNP-type ligands, e.g. N,N′-bis[(2-diphenylphosphino) phenyl] formamidinate, [57][58][59][60] have been widely investigated with respect to their photo-luminescence (PL) properties, the oxygen-based POP analogue has not been considered in this context.…”
Section: Photo-luminescence Propertiesmentioning
confidence: 99%
“…Despite the fact, that transition metal complexes of PNP-type ligands such as Ph 2 PNRPPh 2 (R = Et, 15 C 6 H 5 , 16 2,6-Me 2 C 6 H 3 , 16,17 C 6 H 3 N 2 S), 18 and coordination complexes of related PNNP-type ligands, e.g. N,N′-bis[(2-diphenylphosphino) phenyl] formamidinate, [57][58][59][60] have been widely investigated with respect to their photo-luminescence (PL) properties, the oxygen-based POP analogue has not been considered in this context.…”
Section: Photo-luminescence Propertiesmentioning
confidence: 99%
“…Additionally, gold deviates from its usual linear geometry with an angle of 167.67(10)° (P–Au–mesityl). 68 Complex 45 also demonstrates a rather similar tetranuclear zigzag chain Au–Ag–Ag–Au wherein the intermetallic bond distances are 2.9756(3) Å (Au–Ag) and 2.9009(5) Å (Ag–Ag) and the bond angle is 102.197(13)°. 68…”
Section: P–n Coordinationmentioning
confidence: 98%
“…Molecular structure of 44 in the solid state revealed that each inner lying copper( i ) atom is coordinated to two nitrogen atoms of the amidinate group and to a phosphine unit in an almost T-shaped geometry. 68 The metals arrange themselves in a Au–Cu–Cu–Au zigzag chain with an angle of 111.62(2)° and intermetallic distances of 2.7939(9) Å (Cu–Cu) and 2.9960(4) Å (Au–Cu) which are in the range of metallophilic interactions. Following the HSAB principle, gold coordinates to phosphorous and a mesityl unit.…”
Section: P–n Coordinationmentioning
confidence: 99%
“…Originally, we became interested in alkylene-, arylene-, and dialkylsilanediyl-bridged bis(amidines) as extremely versatile ligands, 16 which have predominantly been employed in Group 1–4, 17–20 13, 21 and 14 22 coordination chemistry, together with related catalytic studies. Applications have also included late transition metals of Groups 8–11 23–26 and the formation of multinuclear complex assemblies with more than two metal centers. 17 c ,25,26 Our findings revealed that these bis(amidine) ligands represent a convenient scaffold for defined linear Cu I cluster arrays 27,28 that were obtained from a tetradentate bis(amidine) 29 and mesitylcopper.…”
Section: Introductionmentioning
confidence: 99%
“…Applications have also included late transition metals of Groups 8–11 23–26 and the formation of multinuclear complex assemblies with more than two metal centers. 17 c ,25,26 Our findings revealed that these bis(amidine) ligands represent a convenient scaffold for defined linear Cu I cluster arrays 27,28 that were obtained from a tetradentate bis(amidine) 29 and mesitylcopper. 30…”
Section: Introductionmentioning
confidence: 99%